Processing apple pomace powder to reduce environmental pollution - Zheplinska, Mariia; Vasyliv, Volodymyr; Zubar, N.; Burova, Zinaida; Mukoid, Roman (My University, 2025)
Яблучний жмих — це відходи, що забруднюють навколишнє середовище та непридатні для годівлі худоби. Різні альтернативні рішення щодо використання яблучного макухи, що реалізуються на практиці, можуть сприяти розвитку технологічного ланцюга безвідходної переробки яблук. Побічний продукт — яблучний макуха — багатий на цінну клітковину у вигляді пектинових речовин. Тому його переробка має велике значення для захисту навколишнього середовища. У статті представлено порівняльний вміст пектину в різних рослинних сировинних матеріалах, а також хімічний склад пектину та елементний склад пектинового порошку в яблучному макусі, що дозволяє використовувати ці відходи як інгредієнт у виробництві харчових продуктів, зокрема, у м'ясній та безалкогольній промисловості, для зниження вмісту цукру та підвищення біологічної цінності продукту. У статті показано можливість використання пектину для виробництва їстівної плівки для захисту харчових продуктів, антимікробних біоплівок, наночастинок тощо, що подовжує термін зберігання харчових продуктів. Досягнення у використанні різних джерел екстракції та знання про структурну модифікацію значно розширили властивості, вихід та сфери застосування пектинових речовин, що містяться в яблучному макусі. Модифікований пектин продемонстрував кращі функціональні властивості, ніж нативний пектин. Встановлено, що пектин може бути використаний у біомедицині як цільовий засіб для доставки біологічно активних ліків. Apple pomace is a polluting waste and is unsuitable for feeding livestock. Various alternative solutions for the use of apple pomace when implemented in practical conditions can contribute to the development of a technological chain of waste-free apple processing. The by-product – apple pomace – is rich in valuable fiber in the form of pectin substances. Therefore, their processing is of great importance for environmental protection. The paper presents a comparative content of pectin in various plant raw materials and the chemical composition of pectin and the elemental composition of pectin powder in apple pomace, which allows these wastes to be used as an ingredient in the production of food products, in particular in the meat and soft drink industries to reduce the amount of sugar and increase the biological value of the product. The article shows the possibility of using pectin for the production of edible film to protect food products, antimicrobial biofilms, nano-particles, etc., which extends the shelf life of food. Advances in the use of different extraction sources and knowledge of structural modification have significantly expanded the properties, yield and applications of pectic substances found in apple pomace. Modified pectin has shown better functional properties than native pectin. It has been established that pectin can be used in biomedicine as a targeted application in the delivery of bioactive drugs and to stop the spread of cancer cells in the lungs. During the review of literature sources, the possibility of using apple pomace in the production of bioethanol was considered, which will positively affect environmental processes in the future. The obtained data contain practical value regarding the possibility of waste-free processing of apple pomace in various sectors of the national economy, which is cur-rently a relevant issue.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; біопаливо; біомедицина; харчове покриття; пектин; sensory; defects; biofuel; biomedicine; food coating; pectin; вичавки яблучні